Analisis Minat Siswa Terhadap Mata Pelajaran Teknologi Informasi dan Komunikasi (TIK) Dengan Pengenalan dan Pelatihan Ketrampilan Dasar Komputer di Sekolah Dasar Negeri Wonoasri 1 Ngadirojo Pacitan - Ali Arifin; Linggar Famukhit (Journal of Social Empowerment, 2019)
Technological advances in the present cannot be denied and avoided again. Technological advances also have a major impact on the education sector. In the field of education, technological advances are utilized to provide new innovations that give progress to the world of education in Indonesia. ICT subjects are one of the subjects that are closely related to technological developments, where ICTs are the pioneers of technological development. The government has set ICTs as compulsory subjects in primary schools as stated in Permendikbud 37 of 2018 Article 2A which states: Information content in SD / MI is used as a learning tool and or is learned through extracurricular and / or local content. In fact, ICT education programs or Informatics Content have not been evenly distributed throughout Indonesia, one of them is Wonoasri 1 Public Elementary School, in the school there are no ICT subjects. Given this, an analysis of how much students interest in information and communication technology (ICT) subjects will be carried out by introducing and training basic computer skills. The method in this study is quantitative. Data collection is done with classroom teaching and tutoring. The results of the study showed that 91,67% of students attended computer introduction and training, it could be concluded that in these schools ICT subjects were very much needed.